COVERAGE OF CULTURAL LIFE IN ZARAFSHAN OASIS NEWSPAPERS - Abdurakhmanov, Abdugaffor (Журнал иностранных языков и лингвистики, 2023)
The article talks about the coverage of cultural life in the newspapers published in Zarafshan Oasis. From the early years of independence, newspapers changed their style and direction in the dissemination of information. The people moved away from Soviet ideology, outdated and practically based on false ideas. The activities of literature and art, science, folk oral creativity, reading culture, shrines and scholars began to be studied on the basis of impartial and original sources. An important role in bringing such changes to the public, introducing people with genuine history was played by regional and network publications in the Zarafshan Oasis.